Jugamos en un circuito de mini maratón - Araujo Araujo, Consuelo Maria (2019)
The present work called "We play in a mini marathon circuit" is focused on the area of psychomotor skills of 5 years old boys, whose design of learning session, theoretical support and pedagogical support are based on the different bibliographic references about of the aforementioned area and also in the documentation provided by the Ministry of Education adding experience in my workplace._x000D_ In the learning session the competition was: it develops autonomously through its motor skills, ability: it includes your body, performance: it recognizes your body sensations, and identifies the needs and changes in the state of your body, such as breathing and sweating He recognizes the parts of his body by relating them to his actions and naming them spontaneously in different everyday situations. It represents your body (or that of another) in its own way, incorporating more details of the human figure, and including some of its own characteristics (short, long, straight, curly hair, etc.). Focusing mainly on: "recognize your body sensations, and identify the needs and changes in the state of your body, such as breathing and sweating." The purpose of this activity is for children to have knowledge of the changes that their body has when participating in a mini marathon circuit._x000D_ We must all understand the importance of psychomotor activities for the development of learning which will allow them to express themselves through their body, movements and changes of state such as agitation after doing it and especially what our body needs at the end of the activity.